2008
DOI: 10.1002/mats.200700067
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of θ (Lower Critical Solution Temperature) in Polymer Solutions Based on 3D Descriptors and Artificial Neural Networks

Abstract: Quantitative structure‐property relationships were studied between descriptors representing the three‐dimensional structures of molecules and θ (LCST, lower critical solution temperature) in polymer solutions with a database of 169 data containing 12 polymers and 67 solvents. Feed‐forward artificial neural networks (ANNs) combined with stepwise multilinear regression analysis (MLRA) were used to develop the models. With ANNs, the squared correlation coefficient (R2) for θ (LCST) of the training set of 112 syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Models of this type have been described in organic solvents, and success is likely when applying this approach to LCSTs in water. [ 45–47 ]…”
Section: Thermodynamics Of the Lcstmentioning
confidence: 99%
“…Models of this type have been described in organic solvents, and success is likely when applying this approach to LCSTs in water. [ 45–47 ]…”
Section: Thermodynamics Of the Lcstmentioning
confidence: 99%
“…This leads to a linear 10-factor model which shows approximately the same predictive power as that developed by Afantitis et al (R 2 = 0.8874, R 2 cv = 0.8658, s = 24.57). In a further paper, Xu et al investigated an even larger descriptor set and the use of neural networks for the prediction of LCSTs [155]. The researchers showed that the development of an initial linear model on the basis of the enlarged descriptor space does not lead to significant improvements in predictive ability in comparison to earlier work, but that the use of neural networks can lead to further improvements in the predictive ability of a model (R 2 = 0.9625, s = 13.43 for the training and R 2 = 0.9524 for the test set).…”
Section: Lower Critical Solution Temperature (Lcst)mentioning
confidence: 99%
“…For example, machine learning models trained on quantum-mechanical data have been used to screen dielectric properties of polymers , and predict atomization energies of molecules, and molecular dynamics simulations of molten and crystal silicon have been conducted with on-the-fly machine learning of quantum-mechanical forces . In addition, ANNs have been used to successfully predict the lower critical solution temperature of polymers, the glass transition temperature, and various other polymer properties. …”
Section: Introductionmentioning
confidence: 99%